EFFECTIVENESS OF FIXED DOSES OF PROPRANOLOL IN THE TREATMENT OF HEMANGIOMAS REGARDLESS OF CHILD’S WEIGHT GAIN: A CASE REPORT - Anger,Jaime (2019)
ABSTRACT Objective: To present the outcomes of fixed doses of propranolol tablets for the treatment of hemangiomas. Case description: Two illustrative cases of hemangioma in infant patients younger than six months old are described. Treatments were started in 2010 and 2011 and were monitored until August 2017. Patients were treated with fixed doses, initially calculated based on the upper limit of 3 mg/kg/day and administrated in two daily doses rounded down to the nearest multiple of five milligrams. Dosage was not adjusted to patients’ weight gain. The tablets were crushed and then diluted in a maximum amount of 3 mL of water. This procedure was necessary because propranolol was not available in oral solution in 2009, when dosages available in the Brazilian market were 10, 40 and 80 mg. Both patients presented significative improvement in the first 60 days and were in complete remission by the end of the treatment. Comments: It is possible to treat patients with Propranolol 10 mg tablets, even though the dosage is not as precise as when calculated according to patients’ weight. The maintenance of a fixed dose, ignoring the patient’s progressive weight gains, helps avoiding the rebound effect and decreases complications.